KAJIAN PERUBAHAN DISTRIBUSI KEKERASAN DAN PERUBAHAN STRUKTUR MIKRO PADA PROSES QUENCH TERHADAP VARIASI DIAMETER DALAM DARI BAJA KARBON SEDANG TIPE SAE 1040 - Romania, Romania; Mizhar, Susri; Yulfitra, Yulfitra; Suherman, Suherman (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
The purpose of this study was to determine the mechanical and microstructure properties of medium carbon steel (carbon steel), namely carbon steel with carbon content (0.30% - 0.60% C); SAE 1040 steel is used as a shaft in a component of a machine. In this study Heatreatment was carried out at a temperature of 850 ° C with a hold time of 2 hours and then cooled quenched on the water cooling medium until it reached room temperature. Then the hardness and microstructure tests were carried out. In this study there were 3 specimens with the highest price of hardness found in specimens with an inner diameter of 30 and a thickness of 20 mm with an average value inside 275.9 HVN, Center 215.06 HVN, and Outside 732.9 HVN. From the observation of the microstructure showed that the SAE 1040 steel that had been in the heatreatment contained ferrite, pearlite, and martensite phases. The results show that the mechanical properties and microstructure are strongly influenced by temperature and holding time.